An investigation into the effectiveness of a manualised group treatment programme for chronic health conditions : a thesis presented in partial fulfillment of the requirements for the degree of Doctorate in Clinical Psychology at Massey University, Manawatu Campus - Aranas, Evelyn Myra Friel (Massey University, 2014)
Chronic health conditions (CHC) such as cardiovascular disease, diabetes, asthma and chronic obstructive pulmonary disease can have a significant psychological impact. Group interventions designed to treat a heterogeneous range of chronic health conditions that are implemented in a naturalistic clinical setting are scarce. Two manualised group interventions were developed based on a biopsychosocial model framework. The pilot manual was amended from participant and staff feedback, and changes were incorporated into the main well-being manual. The present study aimed to explore the effectiveness of the Manualised Group Treatment Programme. A mixed methods approach was used to investigate whether the Manualised Group Treatment Programme was effective in improving quality of life and reducing distress in clients with a chronic health condition. Participant and clinician experiences of the therapeutic groups were studied. Participants’ quality of life and distress as measured by the Hospital Anxiety and Depression Scale, Outcome Rating Scale and Short Form-12 remained stable. A thematic analysis was conducted following semi structured interviews with six clients who attended either the pilot group or main well-being group and the three clinicians who facilitated the programme. The results identified that participants benefited from realising they were not alone with having a CHC and could relate to others who faced difficulties managing their CHC. Participants implemented skills they learned in the group and improved their communication with their health care professionals. However, they were apprehensive about attending the groups and how they would be perceived by others. Participants used downward social comparisons as a way of feeling better. They perceived other group members to be worse off than them. The clinicians’ beliefs about therapeutic groups’ effectiveness changed from considering one-on-one treatment as the only optimum method for therapy delivery. Their core belief remained focused on meeting client needs. Feedback from the clinicians regarding the effectiveness of the manualised programme was positive. They evaluated the programme as fit for its intended use. This study highlights some of the difficulties in implementing evidence based efficacious therapy as it is applied and practiced in a naturalistic clinical setting. The study’s limitations included the low number of participants, as well as the fact that several participants had previous ongoing individual therapy. This affected group processes and how participants regarded each other and their illness. This study has added to the limited health or psychological treatment group literature within New Zealand as well as contributing to the international knowledge base on group centred treatments for chronic health conditions.
Keywords: Chronic diseases; Psychotherapy; Group psychotherapy; Therapy; Treatment; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Applied psychology; Manualised Group Treatment Programme